Towards a sustainable bioclimatic approach for the Peruvian high Andean rural area: Evaluation of the thermal contribution of a greenhouse attached to a dwelling - Molina J.O. (2020)
This study includes the evaluation and validation of two experimental housing modules built in Imata, Arequipa, Peru, at 4500 meters above sea level (masl) and with a very cold climate. The modules are similar, differing only in that one of them has a greenhouse attached to the north wall. The design and materials used in the module envelopes are similar to what is mostly used locally. For the simulation work and the validation of the energetic behavior, both modules were equipped for the acquisition of the temperatures in the interior, and for the simulation, the EnergyPlus software was used. The exchange of air between the module with the greenhouse and its greenhouse was controlled by means of opening and closing the door and window that connected them, using different configurations. When the door and the window are open during daytime, the temperature inside the module can increase 5.7 °C with respect to the module without the greenhouse, and in relation to the external temperature, up to 12.1 °C during the day and up to 16 °C during the night. The data obtained with simulation are in excellent agreement with the data measured inside the two modules for all the proposed configurations. These results strengthen the proposal to use attached greenhouses to obtain sustainable heating for rural high Andean homes which, for the most part, do not have any heating. © 2019. The Authors. Published by International Solar Energy Society Selection and/or peer review under responsibility of Scientific Committee